Dynamical Downscaling of Coastal Dynamics for Two Extreme Storm Surge Events in Japan - Trošelj, Joško; Ninomiya, Junichi; Takewaka, Satoshi; Mori, Nobuhito (Frontiers in Marine Science, 2021)
Hindcasts of the downscaled fine resolution scale coastal dynamics are important to quantitatively analyze variations in storm surge heights, water temperature, salinity and high velocities which induce shoreline changes. This study quantifies the impact of two extreme storm surge events in October 2006 on the Ibaraki Coast in Japan to the coastal Sea Surface Height (SSH), vertically averaged velocity (Vbar), Sea Surface Temperature (SST) and Sea Surface Salinity (SSS) by reproducing hindcasts of the dynamically downscaled coastal dynamics from a 10 km resolution parent dataset (Four-dimensional Variational Ocean ReAnalysis for the Western North Pacific over 30 years, FORA-WNP30) to related 2 km, 667 and 222 m resolution datasets using 3 domain nesting Coupled-Ocean-Atmosphere-Wave-Sediment-Transport Modeling System (COAWST). Validation was made by comparing the SSH, Vbar, SST and SSS modelled results with observed data and discussing differences in their values in the downscaled and the parent datasets. This study concludes that the low-pressure system event on 7th of October had much bigger impact to the SSH and Vbar than the one on 24th of October, which had similar peak of southward surface wind but lower Sea Level Pressure drop, whereas the impact to the SST and SSS was similar. These findings are helpful in understanding and assessing shoreline changes and damages on the well-developed local fishery and seashell industry. Finally, these findings and modelling approach are useful for climate change impact assessment and can ultimately serve as guidelines for developing adaptation policies.